The Effect Of Substituting Inulin Flour, Mocaf (Modified Cassava Flour), And Stevia Sugar (Stevia Rebaudiana) On Fiber Content, Acceptability, And Nutritional Economic Value In Crispy Brownies - Ni Putu Laura Angelina; Annis Catur Adi (CV. AFDIFAL MAJU BERKAH, 2026)
Obesity is a major health problem associated with unhealthy dietary patterns, including excessive consumption of high-calorie and low-fiber snacks. Therefore, the development of healthier snack alternatives is needed to help increase fiber intake and reduce the risk of obesity-related diseases. This study aims to determine the effect of substituting mocaf flour, inulin flour, and stevia sugar on the organoleptic quality, nutritional content, and economic value of brownies crispy as a high-fiber snack alternative for individuals with obesity. This study was a laboratory experimental research using a Completely Randomized Design (CRD) consisting of one control formula (F0) and four modified formulas (F1, F2, F3, and F4). The panelists consisted of 3 expert panelists for the preliminary test and 30 untrained adult panelists aged 19–29 years for the hedonic test. Data were analyzed using the Shapiro-Wilk, Kruskal-Wallis, and Mann-Whitney tests. The results showed no significant differences in aroma, color, and texture characteristics among the formulas (p>0.05), while significant differences were found in taste, aftertaste, and overall acceptance (p<0.05). The selected formula met the BPOM requirements for a high-fiber claim and fulfilled 10–15% of the daily Recommended Dietary Allowance (RDA) per serving, indicating its potential as a healthier snack alternative for adults with obesity.